SIFAT PAPAN PARTIKEL NIR-PEREKAT DENGAN PROSES KEMPA PANAS DARI LIMBAH SERUTAN BAMBU PETUNG (Dendrocalamus asper Backer) - , FITHRY ARDHANY ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Recently, it has become more and more important to minimize environmental pollution. As an attempt to alleviate the environmental problems in materials, new wood based materials without any adhesives and binders have been investigated. Optimizing of petung bamboo waste can be achieved by manufacturing binderless particleboard. Binderless particleboard has been considerable interest in issues regarding the negative side effect of synthetic glues on the environment. This research was designed to analyze their physical and mechanical properties and evaluate the various manufacturing conditions: pretreatment (boiling), pressing temperature and pressing time. The other objectives are to know the alteration of cell properties and the degradation of chemical composition. Binderless particleboards were manufactured from petung bamboo waste (Dendrocalamus asper Backer) by hot pressing process. This study was conducted using Completely Randomized Design into factorial by three conditions: pre-treatment (boiling), pressing temperature (180ºC, 200ºC and 220ºC) and pressing time (10 minutes and 15 minutes). The board properties were evaluated by JIS A 5908-1994 (type-8) as follows: density, moisture content, water absorption, thickness swelling, internal bonding, modulus of rupture, and modulus of elasticity. Chemical analyzes were extractive content, holocelluloses content, α-celluloses content, hemicelluloses content and lignin content. The result showed that single factor pressing time was affected on all of physical properties of binderless particleboard. Degradation of chemical composition occurs during the hot pressing process which affected on cell properties changing. The best properties of binderless particleboard was obtained at 15 minutes highest pressing temperature (220ºC) on particles without boiling, which have density 0,59 g/cm³, moisture content 5,96%, water absorption 34,32%, thickness swelling 2,06%.